Desain Dan Implementasi Data Warehouse Pada Perpustakaan Daerah Provinsi Sumatera Selatan - Nia Adila; Andri Andri (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2021)
This research will focus on processing visitor data, member data, book borrowing data and book return data at the Regional Library of South Sumatra Province. The data is stored in the form of an excel file with a large amount of data, causing problems in the storage system such as data accumulation, data loss, no data analysis and delays in the reporting process. The process of data storage and data retrieval will be well integrated by building a data Warehouse at the Regional Library of South Sumatra Province. Data Warehouse is a system that contains several years of history and facilitates decision making. At the data Warehouse design stage using the Nine-Step method (Kimball, 2002), in this method there are nine steps in designing a data Warehouse, namely Process Selection, Grain Selection, Identification of dimensional adjustments, Fact Selection, Storage of initial calculations in the fact table, Reviewing the dimension table, selecting the database duration, tracking dimension changes, and prioritizing, querying the model and selecting the physical design. And the design and data processing process will use the Pentaho kettle and public Tableau applications, with the design and implementation of the data Warehouse, it is expected to help facilitate the reporting and analysis process for the Regional Library of South Sumatra Province.